Placental Pathology in COVID-19. Issue 1 (22nd May 2020) - Shanes, Elisheva D; Mithal, Leena B; Otero, Sebastian; Azad, Hooman A; Miller, Emily S; Goldstein, Jeffery A
Abstract: Objectives: To describe histopathologic findings in the placentas of women with coronavirus disease 2019 (COVID-19) during pregnancy. Methods: Pregnant women with COVID-19 delivering between March 18, 2020, and May 5, 2020, were identified. Placentas were examined and compared to historical controls and women with placental evaluation for a history of melanoma. Results: Sixteen placentas from patients with severe acute respiratory syndrome coronavirus 2 (SARS - CoV - 2) were examined (15 with live birth in the third trimester, 1 delivered in the second trimester after intrauterine fetal demise). Compared to controls, third trimester placentas were significantly more likely to show at least one feature of maternal vascular malperfusion (MVM), particularly abnormal or injured maternal vessels, and intervillous thrombi. Rates of acute and chronic inflammation were not increased. The placenta from the patient with intrauterine fetal demise showed villous edema and a retroplacental hematoma. Conclusions: Relative to controls, COVID-19 placentas show increased prevalence of decidual arteriopathy and other features of MVM, a pattern of placental injury reflecting abnormalities in oxygenation within the intervillous space associated with adverse perinatal outcomes. Only 1 COVID-19 patient was hypertensive despite the association of MVM with hypertensive disorders and preeclampsia. These changes may reflect a systemic inflammatory or hypercoagulable state influencing placental physiology.